Dampak Kenaikan Harga Tiket Pesawat Udara Terhadap Minat Pengguna Jasa Penerbangan di Bandar Udara Sultan Babullah Ternate - Inaya Hi Abd Rahman; Adipura Danang Maulana (Universitas Sains dan Teknologi Komputer, 2023)
The factor that most influences passengers in purchasing goods or services is the price factor, where the cheaper the price offered, the attractiveness of the purchase will increase. Air transportation rates are currently regulated by Law No. 1 / 2009 concerning Lower Limit Tariffs (TBB) and Upper Limit Tariffs (TBA). This is done so that service rates do not fall or soar high. The demand for plane tickets changes every year, it can go up and down at any time. This is caused by the price level which is always changing all the time. Price is one of the factors that influences demand for plane tickets. This research uses quantitative data. The data used in this research was taken based on a questionnaire distributed to passengers at Sultan Babullah Airport in Ternate. The data analysis techniques used are simple linear regression analysis, T test, and coefficient of determination. The research results show that based on the research and data testing that has been carried out, the results on the coefficient of determination value can be concluded that the increase in ticket prices on service user interest at Sultan Babullah Ternate airport is 78%. The remaining 22% was caused by other factors not examined by researchers.